The bromodomain interaction module. - Filippakopoulos, P; Knapp, S (2012)
ε-N-acetylation of lysine residues (K(ac)) is one of the most abundant post-translation modifications (PTMs) in the human proteome. In the nucleus, acetylation of histones has been linked to transcriptional activation of genes but the functional consequences of most acetylation events and proteins recruited to these sites remains largely unknown. Bromodomains (BRDs) are small helical interaction modules that specifically recognize acetylation sites in proteins. BRDs have recently emerged as interesting targets for the development of specific protein interaction inhibitors, enabling a novel exiting strategy for the development of new therapies. This review provides an overview over sequence requirements of BRDs, known substrates and the structural mechanisms of specific K(ac) recognition.